Surface reconstructions of Fe3 O4 (001) - Mariotto, Guido (Trinity College (Dublin, Ireland). School of Physics, 2002)
In this thesis, the (001) surface of magnetite artificial single crystals has been studied using low-energy electron diffraction (LEED), Auger electron spectroscopy (AES) and Scanning Tunneling Microscopy (STM). STM investigations were carried out in constant current mode at room temperature using non-magnetic tips (PtIr and W) and antiferromagnetic tips (MnNi). Extensive investigation was used to find an adequate sample preparation procedure. Although several methods have been proposed, ranging from in-situ cleavage to annealing in Ultra High Vacuum (UHV) or in an oxygen partial pressure, to Ar+ sputtering, each of these methods has drawbacks, and the preparation parameters (such as annealing temperature and oxygen partial pressure) may vary drastically according to the type of system used, whether single crystals or thin films.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin